Perbankan dalam Dimensi Konvensional dan Syariah - Yuliatin Yuliatin (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2012)
Islamic financial institutions are generally and Islamic banks particularly has become an interesting phenomenon in two or three decades. Institutions and Islamic banks are believed to be an interesting fact, compared with the conventional financial system. Now, people are witnessing the rise of Islamic financial institutions, particularly in the form of an Islamic bank, which running system and the division of profits and eliminate various interests. This illustration appears not only in Islamic countries but also almost in the world, including Indonesia. This fact indicates that the demands on Islamic banks and services are needed to meet the needs the Islamic community in performing daily activities with Islamic Sharia